Double-Voiced Discourse in Susan Glaspell's "Trifles" - Yulistiyanti Yulistiyanti; Agnes Widyaningrum; Endang Yuliani Rahayu (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2020)
This research reveals double-voiced discourse in dialogues of Susan Glaspell’s Trifles. This research is categorized as a qualilative study. The data was taken from Glaspell’s Trifles text and indentified by applying Bakhtin’s double-voiced discourse (1981) and Baxter’s double-voiced discource functions (2014). It also applied Kate Millet’s Sexual Politics (2000) and Putnam Tong’s Feminist Thought (2009) to interpret the ideologies found in the text. There are thirteen double-voiced discourses found in Trifles. They represent two opposite ideologies; patriarchy and feminism delivered by the male and female characters. The discourses show personal power, debate ideas, and building solidarity. The male character uses the discourse to display personal power. Meanwhile, the female characters use the discourses to debate ideas and build their solidarity as women.